Metabolic Acidosis Improves Airway Conductance in Patients with Asthma - Brijker, F.; Van Den Elshout, F. J.J.; Bosch, F. H.; Heijdra, Y. F.; Folgering, H. Th.M. (The Journal of asthma, 2009)
The objective was to investigate whether acute metabolic acidosis could cause bronchodilation in patients with asthma. Twelve patients with asthma (8 females, mean age 39 (± SD 12) years, forced expiratory volume in 1 second [FEV1] 93 [±9] % predicted, PC20 1.9 (±1.0) mg/mL) participated in a double-blind, placebo-controlled trial. Subjects ingested calculated amounts of ammonium chloride to induce acidosis or saline as placebo, in random order, each on a separate day. Airway resistance (Raw), specific airway conductance (sGaw), FEV1, and PEF were measured as primary variables. To evaluate the consequences of alterations in bronchial contractility on the airway responsiveness, the histamine provocation test (PC20) was measured as secondary variable. The intervention resulted in a mean (SD) decrease in base excess from -0.5 (±1.4) to -3.9 (±1.1) mmol/L (p < 0.01) and a decrease in pH from 7.41 (±0.02) to 7.36 (±0.02) (p < 0.01). This caused a statistically significant increase in sGaw from 1.15 (±0.16) to 1.26 (±0.13) 1/kPa.s) (p < 0.05). Tendencies towards increase were found in PEF (7.79 (±2.2) versus 8.09 (±1.9) (NS, p = 0.10) and in FEV1 (2.98 (±0.9) versus 3.06 (±0.9) (NS, p = 0.15). PC20 did not change significantly. It was concluded that acute metabolic acidosis has a modest bronchodilating effect in patients with asthma.